BUDAYA LITERASI DAN PENINGKATAN KETERAMPILAN BERPIKIR KRITIS DI ERA INDUSTRI 4.0: EKSPLORASI POTENSI KOLABORASI SEKOLAH DAN KOMUNITAS - Asnal Mala (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2021)
The purpose of this study was to determine the role of teachers and principals in increasing literacy culture in Al-Chusnaini Klopohten Islamic Middle School-Sukodono-Sidoarjo as an effort to improve critical thinking skills, to determine the supporting and inhibiting factors in increasing literacy culture in Ak-Chusnaini Klopohten Islamic Middle School- Sukodono-Sidoarjo, knowing the strategies to increase literacy culture in increasing interest in reading at Al-Chusnaini Islamic Middle School Klopohten-Sukodono-Sidoarjo. This study uses a qualitative approach with this approach to produce descriptive data in the form of books (Risearch libraries) or verbally from people and observable behavior. The results of this study indicate that: 1) The role of the classroom teacher is as an educator, manager, administrator, supervisor, leader, innovator and motivator. 2) There are several supporting and inhibiting factors in developing a literacy culture. Supporting factors include the active role of students in school, support from parents of students. In addition, there are several inhibiting factors, namely: collection limitations, and the influence of technology. 3) In developing a literacy culture, teachers at SMP Islam Ak-Chusnaini Klopohten-Sukodono-Sidoarjo have several strategies used, including developing a library, providing fiction, non-fiction, and reference books. Development of reading areas, 15-minute reading program, Development of literacy-themed madrasah activity programs.